Practical Swift - Downey, Eric (Apress : Imprint: Apress, 2016)
This is the ideal guide to walk you through Xcode and all the latest features Swift 3 has to offer. If you have picked up this book, chances are you know a little bit about Swift Programming. With Practical Swift you'll develop an advanced understanding of the language that will enable you to create a reference guide using Xcode Playgrounds, one you can continue to grow throughout your iOS career. You'll learn a myriad of skills and concepts, including topics such as Protocol Oriented Programming (POP), Architecture, Testing, and Generics. You'll also see how Swift has evolved over the years. Practical Swift not only shows you how to code in a clean and concise manner, but also the why behind the code. Understanding why will be instrumental in your advancement as a Swift developer. Finally, all of your newfound knowledge will culminate in building your own iOS app!